Phenotypic characterization of East African goats in Baringo District of Kenya - Indetie, D.; Karimi, S.; Wandera, F.; Lebbie, S.H.B.; Okeyo Mwai, Ally (Institut National de la Recherche Agronomique, 2000)
Survival of indigenous goats in Kenya is at risk: due to exotic breed importation and indiscriminate crossbreeding. Phenotypic description of goats with an aim of determining their improvement, utilization and conservation is important. Phenotypic characteristics of 139 East African Goats were recorded in Baringo District. The goats were categorized by dentition (milk, young, mature). Measurements included liveweight, heart girth., withers height, back., tail, ear, toggle and horn lengths. Toggles and polledness were observed in 2% and 6% of the flock. respectively. Brown coat colour was seen in 32% while black skin colour occurred in 78% of the goats respectively. Milk teeth goats had correlations of 0.94, 0.77 and 0.82 (P<0.05) for weight with heart girth, withers height and back length while mature goats showed correlations of 0.41, 0.12 and 0.12, respectively. A stepwise regression of body weight on linear measurements for young goats included heart girth and withers height with an R2 of 0.61. Only heart girth was included for mature goats with an R2 of '0.18. Proportions of weight to girth were 3.5, 2.9, 2.4 for milk, young and mature goats, respectively. Similar trends were exhibited for weight with other measurements. Withers to Girth proportion was 0.93, 0.94 and 0.91 for milk, young and mature goats respectively. Linear measurements are good predictors of liveweight and therefore indicators for performance. The wide variations of observed parameters shows a need of developing several breeds of varying potentials.